Illness Cognition and Treatment Delay in Patients with Diabetes Mellitus - Vicka Anataya Gabiella Lasi; Helga J. N. Ndun; Eryc Z. Haba Bunga; Marni - (Journal of Health and Behavioral Science, 2026)
Introduction Delayed treatment seeking among patients with diabetes mellitus remains a major challenge to effective disease management and complication prevention. Aim This study explored patients’ perceptions of diabetes mellitus and factors contributing to treatment delay using the Common-Sense Model. Data were collected through in-depth interviews and analyzed using deductive thematic analysis. Result Findings revealed limited understanding of the causes, symptoms, and complications of diabetes mellitus. Early symptoms were often perceived as normal or non-serious, reducing timely healthcare seeking. Participants commonly believed the disease could be managed through dietary modification and traditional remedies, often prioritizing these approaches over medical treatment. Delayed treatment seeking was further influenced by low perceived severity and environmental factors. Conclusion Patients delaying treatment hold an illness cognition defined by symptom normalization, a preference for traditional management, and a minimized perception of disease seriousness, highlighting the need for targeted health education to promote timely care.